2022
DOI: 10.31557/apjcp.2022.23.5.1483
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Salivary Biomarkers in Detecting Early Oral Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Background: Biopsy is the gold standard for oral squamous cell carcinoma (OSCC) diagnosis. Salivary biomarkers provide promising complementary alternative diagnostic adjunct for its simple non-invasive collection and technique and to screen large population. Objective: To summarize and compare the existing evidence on diagnostic accuracy of salivary biomarkers with their estimation method in detecting early oral squamous cell carcinoma. Methods: The review protocol is registered under PROSPERO(CRD42021225704).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In 2022, Shaw et al [ 168 ] meta-analyzed the scientific literature for the quantitative analysis of diagnostic accuracy and applicability of four classes of salivary biomarkers and the relative capability of polymerase chain reaction (PCR) and the enzyme-linked immunosorbent assay (ELISA) to detect them in the saliva. The authors reported results of detecting salivary biomarkers better by PCR than by ELISA; furthermore, the more sensitive and specific biomarkers associated with OSCC were mRNAs, miRNA, and IL-8 (sensitivity and specificity over 89%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Shaw et al [ 168 ] meta-analyzed the scientific literature for the quantitative analysis of diagnostic accuracy and applicability of four classes of salivary biomarkers and the relative capability of polymerase chain reaction (PCR) and the enzyme-linked immunosorbent assay (ELISA) to detect them in the saliva. The authors reported results of detecting salivary biomarkers better by PCR than by ELISA; furthermore, the more sensitive and specific biomarkers associated with OSCC were mRNAs, miRNA, and IL-8 (sensitivity and specificity over 89%).…”
Section: Resultsmentioning
confidence: 99%
“…In the field of omics sciences, the role of salivary proteins associated with OSCC has been widely investigated. Various systematic reviews and meta-analyses have recently summarized this research topic’s state of the art [ 168 , 169 , 170 , 171 , 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies would also be needed to confirm the reliability of salivary screening tests, with an increase in the sample size and multicenter studies, with a combination of several cytokines, and standardized quantification of the same, using reliable and quality reagents, in addition to paired control patients, according to their periodontal health. Shaw et al (2022), in their systematic review and meta-analysis using 13 studies with a total of 1048 patients, found that most of the eight salivary biomarkers (mRNA, miRNA, DUSP100, s100P, IL-8, IL-1B, TNF-a and MMP-9) evaluated in the studies showed good diagnostic accuracy. The authors reported that the detection of mRNA and micro-RNA had a sensitivity of 91% and specificity of 90% when they were detected by the PCR (polymerase chain reaction) technique.…”
Section: Salivary Diagnosismentioning
confidence: 99%
“…The use of such biomarkers in detecting HNSCC is still a developing field. Previous studies have reported up/down-regulation of various salivary miRNAs in HNSCC at various stages of disease (15), with sensitivity and specificity of different miRNAs ranging anywhere 14-100% and 38-100% respectively in detecting HNSCC (16). However, there is still not much known about the expression of miRNA by HNSCC in vitro nor miRNA expression difference dependence on HPV status.…”
mentioning
confidence: 99%